Brexanolone as adjunctive therapy in super‐refractory status epilepticus. Issue 3 (11th September 2017) - Rosenthal, Eric S.; Claassen, Jan; Wainwright, Mark S.; Husain, Aatif M.; Vaitkevicius, Henrikas; Raines, Shane; Hoffmann, Ethan; Colquhoun, Helen; Doherty, James J.; Kanes, Stephen J.
Abstract : Objective: Super‐refractory status epilepticus (SRSE) is a life‐threatening form of status epilepticus that continues or recurs despite 24 hours or more of anesthetic treatment. We conducted a multicenter, phase 1/2 study in SRSE patients to evaluate the safety and tolerability of brexanolone (USAN; formerly SAGE‐547 Injection), a proprietary, aqueous formulation of the neuroactive steroid, allopregnanolone. Secondary objectives included pharmacokinetic assessment and open‐label evaluation of brexanolone response during and after anesthetic third‐line agent (TLA) weaning. Methods: Patients receiving TLAs for SRSE control were eligible for open‐label, 1‐hour brexanolone loading infusions, followed by maintenance infusion. After 48 hours of brexanolone infusion, TLAs were weaned during brexanolone maintenance. After 4 days, the brexanolone dose was tapered. Safety and functional status were assessed over 3 weeks of follow‐up. Results: Twenty‐five patients received open‐label study drug. No serious adverse events (SAEs) were attributable to study drug, as determined by the Safety Review Committee. Sixteen patients (64%) experienced ≥1 SAE. Six patient deaths occurred, all deemed related to underlying medical conditions. Twenty‐two patients underwent ≥1 TLA wean attempt. Seventeen (77%) met the response endpoint of weaning successfully off TLAs before tapering brexanolone. Sixteen (73%) were successfully weaned off TLAs within 5 days of initiating brexanolone infusion without anesthetic agent reinstatement in the following 24 hours. Interpretation: In an open‐label cohort of limited size, brexanolone demonstrated tolerability among SRSE patients of heterogeneous etiologies and was associated with a high rate of successful TLA weaning. The results suggest the possible development of brexanolone as an adjunctive therapy for SRSE requiring pharmacological coma for seizure control. Ann Neurol 2017;82:342–352